2010
DOI: 10.1016/j.pmrj.2010.06.013
|View full text |Cite
|
Sign up to set email alerts
|

The Biopsycho‐ecological Paradigm: A Foundational Theory for Medicine

Abstract: The current biomedical and psychosocial frameworks that form the conceptual basis of medicine today are insufficient to address the needs of the medically complex and environmentally challenged populations of patients often cared for by physical medicine and rehabilitation specialists. The expanded biopsycho-ecological model of health, illness, injury, and disability operating through mechanisms of Health Environmental Integration (HEI) encourages a more complete understanding of illness, injury, activity limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 79 publications
1
70
0
3
Order By: Relevance
“…Combinations of ADL and IADL stages reflect patterns of participation relating to the co-occurrence of difficulties with self-care, and essential interactions with home and community environments (i.e., domestic life). 19 Staging is not intended to replace descriptions of limitations across individual ADLs and IADLs or other approaches to measurement. 27 Knowledge about difficulties with individual tasks is essential when establishing detailed care plans for an individual.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combinations of ADL and IADL stages reflect patterns of participation relating to the co-occurrence of difficulties with self-care, and essential interactions with home and community environments (i.e., domestic life). 19 Staging is not intended to replace descriptions of limitations across individual ADLs and IADLs or other approaches to measurement. 27 Knowledge about difficulties with individual tasks is essential when establishing detailed care plans for an individual.…”
Section: Discussionmentioning
confidence: 99%
“…17 These explanatory hypotheses 18 establish the degree to which IADL stages are associated with other observable variables that theoretically should relate to additional concepts. 16,19 Recognized as fundamental to rehabilitation practices, 20 the biopsycho-ecologic model expands on the biomedical and biopsychosocial models 21 addressing how environmental elements, along with illness and injury-related impairments, link to disability. We expect that higher stages of ADL limitation will be associated with older age and perceptions of poor health.…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…Yet, the apparent shift in relative difficulties among ADLs highlights the importance of periodically re-deriving stages and other functional measures that reflect hierarchies. It is essential to recognize that the physical and social living environments are not static, and that environmental changes in the population [33] could be associated with the evolution of self-reported abilities and disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…With reference to another element, Masala and Petretto [17] concluded that the dynamic nature of the person-environment interaction process was not appropriately captured in the ICF. Stineman and Striem [18] proposed a biopsycho-ecological paradigm as a more inclusive model of the biopsychosocial model expanding the contribution of the physical environment to the interaction of elements defining human functioning.…”
Section: Icf: Lessons Learnedmentioning
confidence: 99%